2001
DOI: 10.1002/app.1531
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic study of effect of steam and carbon dioxide activation on microstructure of polyacrylonitrile‐based activated carbon fabrics

Abstract: This work presents the different effects of steam and carbon dioxide activation on the microstructure of an oxidized polyacrylonitrile (PAN) fabric. An investigation was conducted on a series of carbonized fabrics and two series of activated carbon fabrics. The fabrics were activated by steam and carbon dioxide using heat‐treatment temperatures of 900–1100°C. Steam and carbon dioxide developed the microstructure initially present in the PAN‐based activated carbon fabrics, but with different effects. These fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…[ 35 ] Raman peaks corresponding to the G-band (1584 cm − 1 ) and D-band (1352 cm − 1 ) of the carbon layers can be observed in both of the graphs, with and without oxide deposition. [ 36 ] The XRD and the Raman spectra show the crystallinity and purity of the V 2 O 5 . In the Raman spectrum, there is no characteristic peak from VO 2 (i.e., from the vanadium + 4 oxidation state), whereas V 2 O 5 peaks are present, [ 37 ] which clearly indicates the phase purity of the V 2 O 5 .…”
Section: Structural Characterization: X-ray Diffraction (Xrd) Raman mentioning
confidence: 99%
“…[ 35 ] Raman peaks corresponding to the G-band (1584 cm − 1 ) and D-band (1352 cm − 1 ) of the carbon layers can be observed in both of the graphs, with and without oxide deposition. [ 36 ] The XRD and the Raman spectra show the crystallinity and purity of the V 2 O 5 . In the Raman spectrum, there is no characteristic peak from VO 2 (i.e., from the vanadium + 4 oxidation state), whereas V 2 O 5 peaks are present, [ 37 ] which clearly indicates the phase purity of the V 2 O 5 .…”
Section: Structural Characterization: X-ray Diffraction (Xrd) Raman mentioning
confidence: 99%
“…[211][212][213][214][215][216] The electrodeposition technique was considered to be among the most useful techniques to deposit conducting polymers, such as PANI, on different carbon materials to fabricate different types of PANI/carbon composites. [227,228] 6. A porous carbon nanofiber paper electrode without any binder or percolator was obtained by activation of PAN-based nanofiber paper at temperatures from 700 to 1000 8C in a CO 2 atmosphere.…”
Section: Composites Of Activated Carbon Materialsmentioning
confidence: 99%
“…ACF can be produced from coal [11] and petroleum pitches [12,13], rayon [14], polyacrylonitrile (PAN) [15][16][17] and phenolic resin [18] through high temperature gasification in steam or CO 2 . Ko et al [19] reported that steam was better than CO 2 for generating a well-distributed surface area of ACF. Chemical activation by NaOH, KOH, H 3 PO 4 or ZnCl 2 , however, has not been recommended because despite enhancing the porosity, the reagent may also destroy the fiber morphology [17,20].…”
Section: Introductionmentioning
confidence: 98%